Improving the indoor air quality by using a surface emissions trap. (April 2015) - Markowicz, Pawel; Larsson, Lennart
Abstract: The surface emissions trap, an adsorption cloth developed for reducing emissions of volatile organic compounds and particulate matter from surfaces while allowing evaporation of moisture, was used to improve the indoor air quality of a school building with elevated air concentrations of 2-ethyl-1-hexanol. An improvement of the perceived air quality was noticed a few days after the device had been attached on the PVC flooring. In parallel, decreased air concentrations of 2-ethyl-1-hexanol were found as well as a linear increase of the amounts of the same compound adsorbed on the installed cloth as observed up to 13 months after installation. Laboratory studies revealed that the performance of the device is not affected by differences in RH (35–85%), temperature (30–40 °C) or by accelerated aging simulating up to 10 years product lifetime, and, from a blinded exposure test, that the device efficiently blocks chemical odors. This study suggests that the device may represent a fast and efficient means of restoring the indoor air quality in a building e.g. after water damage leading to irritating and potentially harmful emissions from building material surfaces indoors. Highlights: A surface emissions trap reduced moisture-driven emissions from PVC flooring. The device decreased significantly the perceived odor from a chemicals mixture. RH and temperature did not affect the product's performance. Accelerated aging simulating 10 years device lifetime did not affect its performance. The device may represent a new tool for improving the indoor air quality.